GAMES AS WARMING UP ACTIVITIES IN YOUNG LEARNERS’ CLASSROOMS AT AN ENGLISH COURSE - Noviani Aisyatin (Journal of English and Education, 2014)
The present research aimed at investigating types of games used by a teacher as warming-up activities in young learners’ classrooms. The research involved a teacher of an English course and her young learner students. The data were collected by using observation and interview. The collected data were analyzed by using qualitative method. According to the result of data collection and data analysis, it was found that the teacher applied some types of games proposed by Hadfield (2001) and Evans (1979) as warming-up activities. It is recommended that English teachers apply games as warming-up activities in young learners’ classrooms since games are fun for children and help both students and teachers in teaching learning process. Keywords: Young Learners, Games, Warming-Up Activities